The acute phase management of spinal cord injury affecting polytrauma patients: the ASAP study - Picetti, Edoardo; Iaccarino, Corrado; Coimbra, Raul; Abu-Zidan, Fikri; Tebala, Giovanni D.; Balogh, Zsolt J.; Biffl, Walter L.; Coccolini, Federico; Gupta, Deepak; Maier, Ronald V.; Marzi, Ingo; Robba, Chiara; et al. (World journal of emergency surgery, 2022)
Few data on the management of acute phase of traumatic spinal cord injury (tSCI) in patients suffering polytrauma are available. As the therapeutic choices in the first hours may have a deep impact on outcome of tSCI patients, we conducted an international survey investigating this topic.